2021
DOI: 10.1111/cmi.13339
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa ExoT induces G1 cell cycle arrest in melanoma cells

Abstract: Recently, we demonstrated that Pseudomonas aeruginosa Exotoxin T (ExoT) employs two distinct mechanisms to induce potent apoptotic cytotoxicity in a variety of cancer cell lines. We further demonstrated that it can significantly reduce tumour growth in an animal model for melanoma. During these studies, we observed that melanoma cells that were transfected with ExoT failed to undergo mitosis, regardless of whether they eventually succumbed to ExoT-induced apoptosis or survived in ExoT's presence. In this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Recognition of microbial pathogens by PRRs sets in motion multiple signalling cascades that culminate in the production of proinflammatory cytokines, which recruit effector innate immune leukocytes, particularly neutrophils; those, in turn, destroy invading pathogens by various direct or indirect mechanisms such as phagocytosis, bursts of ROS, AMP production and NETs (Brinkmann et al, 2004;Dovi et al, 2004). Unfortunately, pathogens have evolved various mechanisms to dampen innate immune responses, blocking production of pro-inflammatory cytokines as well as inducing cell death and blocking proliferation in target host cells (Faure et al, 2014;Hornef et al, 2002;Lai et al, 2009;Mohamed et al, 2021;Shafikhani and Engel, 2006;Shafikhani et al, 2008;Tolle et al, 2015;Wood et al, 2015a;Wood et al, 2015b). The study hypothesis was that local administration of immunomodulators that can accelerate and direct innate immune leukocyte responses (particularly neutrophils) toward the site of the surgically placed implant would enhance the immune responses toward infection and be effective in reducing PJI, even in the absence of prophylactic antibiotics.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of microbial pathogens by PRRs sets in motion multiple signalling cascades that culminate in the production of proinflammatory cytokines, which recruit effector innate immune leukocytes, particularly neutrophils; those, in turn, destroy invading pathogens by various direct or indirect mechanisms such as phagocytosis, bursts of ROS, AMP production and NETs (Brinkmann et al, 2004;Dovi et al, 2004). Unfortunately, pathogens have evolved various mechanisms to dampen innate immune responses, blocking production of pro-inflammatory cytokines as well as inducing cell death and blocking proliferation in target host cells (Faure et al, 2014;Hornef et al, 2002;Lai et al, 2009;Mohamed et al, 2021;Shafikhani and Engel, 2006;Shafikhani et al, 2008;Tolle et al, 2015;Wood et al, 2015a;Wood et al, 2015b). The study hypothesis was that local administration of immunomodulators that can accelerate and direct innate immune leukocyte responses (particularly neutrophils) toward the site of the surgically placed implant would enhance the immune responses toward infection and be effective in reducing PJI, even in the absence of prophylactic antibiotics.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Mice were anaesthetised using 2 % isoflurane. A total of 5 µL of fMLP solution or vehicle control was injected into the right hindlimb knee joint using a 5 µL Hamilton ® syringe (Hamilton, 7634-01) and 27-Gauge needle, as previously described (Nagao et al, 2017).…”
Section: Intra-articular Injectionmentioning
confidence: 99%
“…Data of cell cycle analysis obtained from flow cytometry revealed that our recombinant IT arrests the HepG2 cell cycle at the G2 phase. Previous studies have been shown that ITs can impress cell cycles at G1/S phases [42][43][44]. Correlation among DNA fragmentation, apoptosis, and cell cycle arrest has been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We performed Western immunoblotting on cell lysates or on tissue lysates, using the indicated antibodies as we described previously ( 27, 71, 80 ). Equal amounts of proteins (as determined by BCA analysis) were loaded.…”
Section: Methodsmentioning
confidence: 99%